2013
DOI: 10.1177/0957650913499749
|View full text |Cite
|
Sign up to set email alerts
|

Flow separation impacts on the hydrodynamic performance analysis of a marine current turbine using CFD

Abstract: Although there are different strategies to control the operation of marine turbines, the so-called ‘stall-regulated strategy’ is one of the most widely used and mature control strategies. Since the stall phenomenon is closely related to flow separation around the turbine blades the treatment of this separation requires great care during the design and performance analysis of turbines when using computational fluid dynamics (CFD). This study investigates appropriate methodologies and approaches to simulate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 11 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…In this paper a typical three bladed HATT was chosen for the study. This turbine model was designed and tested during a previous project (Wang et al, 2007) and validated by a CFD study (Shi et al, 2013). The main parameters of the notional full-scale design are given in Table 1.…”
Section: Brief Introduction To Selected Tidal Turbinementioning
confidence: 99%
“…In this paper a typical three bladed HATT was chosen for the study. This turbine model was designed and tested during a previous project (Wang et al, 2007) and validated by a CFD study (Shi et al, 2013). The main parameters of the notional full-scale design are given in Table 1.…”
Section: Brief Introduction To Selected Tidal Turbinementioning
confidence: 99%
“…14 The downstream turbine operated at increased TSR due to the reduced inflow velocity and 15 showed lower performance with higher variations (Fig. 5) however, the turbine blade design 16 was shown previously to maintain high and practically constant CT values over a range of TSR 1 expected to be encountered by the upstream and downstream turbine [27]. The detailed 2 performance of array turbines will be further investigated further numerically.…”
Section: Single Device Wake Measurementsmentioning
confidence: 89%
“…Reynolds number in the ECT is almost three times higher than in the HIT water channel the impact of the Reynolds number on the results appeared to be limited. Only 0.75% difference can be found at TSR=5.5 when the turbine reached to the maximum power coefficient (Shi et al, 2013).…”
Section: Turbine Performance Without Diffusermentioning
confidence: 93%
“…This was a 3-bladed horizontal axial turbine using symmetrical and bi-directional airfoil blade sections. These sections are classified as BDA65-21 and BDA66-12 (Guo et al, 2013;Shi et al, 2013), which were adopted from NACA 65-21 and NACA 66-12, respectively, as shown in Fig.2. The open water performance of the turbine was verified experimentally using a 300mm diameter model turbine which was initially tested in the Emerson Cavitation Tunnel (ECT) of Newcastle University, UK (Atlar, 2011) and later in the circulating water channel of Harbin Institute of Technology (HIT), in China.…”
Section: Turbine Performance Without Diffusermentioning
confidence: 99%